Hepatitis delta virus propagation enabled by hepatitis C virus—Scientifically intriguing, but is it relevant to clinical practice? - Pflüger, Lisa Sophie; Schulze zur Wiesch, Julian; Polywka, Susanne; Lütgehetmann, Marc (Journal of viral hepatitis, 2021)
In vitro cell culture experiments and animal models have demonstrated that hepatitis delta virus (HDV) can theoretically propagate being enveloped by human pathogenic viruses other than hepatitis B virus (HBV), namely hepatitis C virus (HCV) and dengue virus. However, the clinical relevance of these findings and whether HDV replication occurs in real‐world hepatitis B surface antigen (HBsAg)–negative HCV patient cohorts remain unknown. To this aim, we analysed 323 HCV‐RNA–positive and HBsAg‐negative sera for the presence of HDV‐RNA and anti‐HDV antibodies (anti‐HDV). All 323 (100%) samples were negative for HDV‐RNA. Interestingly, 8/316 samples tested positive for anti‐HDV. The HBV serology of these eight patients showed a positive result for HBV core antibodies (anti‐HBc) indicating a seroconversion of an acute HBV infection in the past. None of the anti‐HBc–negative patients were positive for anti‐HDV. Our results indicate a distinctly low probability of replicative HDV infection in HCV mono‐infected patients in Germany. Current German clinical guidelines rightly recommend performing HDV screening only in HBsAg‐positive patients. However, larger studies on this subject should be performed in regions that are endemic for chronic HBV/HDV as well as HCV infections.